Aggregated neutrophil extracellular traps occlude Meibomian glands during ocular surface inflammation - Mahajan, Aparna; Hasíková, Lenka; Hampel, Ulrike; Grüneboom, Anika; Shan, Xiaomei; Herrmann, Irmgard; Garreis, Fabian; Bock, Felix; Knopf, Jasmin; Singh, Jeeshan; Mahajan, Siddharth; Leppkes, Moritz; et al. (Ocular Surface, 2021)
Purpose: Obstructive Meibomian gland dysfunction (MGD) is one of the leading causes of evaporative dry eye disease. Meibomian glands at the eyelid secrete lipids that prevent evaporation of the aqueous tear film. The pathogenesis of obstructive MGD is incompletely understood to date. Herein, we aim to investigate the pathogenesis of obstructive MGD using murine and human samples with various forms of ocular surface inflammation. Method: The presence of Neutrophil extracellular Traps (NETs) was detected with immunofluorescence analysis of ocular surface discharge and biopsy samples from patients with blepharitis. Tear fluid from patients with MGD and blepharitis were evaluated for the presence of inflammatory mediators using bead based immunoassay. Murine model of allergic eye disease (AED) was performed to investigate the role of NETs in MG occlusion. Results: we show that the ocular discharge from patients with blepharitis contains aggregated neutrophil extracellular traps (aggNETs). Furthermore, the ducts of human Meibomian glands affected by blepharitis were largely congested by aggNETs. Tear fluid from patients with MGD showed elevated neutrophil chemoattractants (C5a, IL6, IL8 and IL18). C5a and IL8 correlated with the degree of deficiency of tear fluid. In the murine model of allergic eye disease (AED), aggNETs accumulated in the MG leading to occlusion of their ducts and the retrograde pent-up of the fluid followed by acinar atrophy. Constraining aggNET formation by genetic or pharmacological inhibition of peptidyl arginine deiminase type 4 (PADI4) effectively reduced MG damage. Conclusion: We conclude that aggNETs occlude MG causing MGD after ocular surface inflammation.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Blepharitis; Meibomian gland dysfunction (MGD); Neutrophil extracellular traps (NETs); Occlusion

Alpha- and beta-melanocyte stimulating hormone positively impact lipogenesis of meibomian gland cells in vitro and ex vivo - Zahn, Ingrid; Socher, Eileen; Bergua, Antonio; Schikorra, Thilo; Kleinsasser, Benedikt; Garreis, Fabian; Schicht, Martin; Dietrich, Jana; Paulsen, Friedrich (Biomedicine & Pharmacotherapy, 2025)
Purpose The meibomian glands produce a lipid-rich secretion that forms the superficial layer of the tear film, preventing excessive evaporation. Dysfunction of these glands (MGD) is the primary cause of dry eye disease (DED), a growing public health concern. Currently, there are limited pharmacological treatments for DED. However, α-/β-melanocyte-stimulating hormones (α-/β-MSH), ligands of the melanocortin receptors (MCR), are known to regulate lipogenesis and differentiation in sebaceous glands. This study investigated the influence of α-/β-MSH on exocrine secretion in human meibomian glands. Methods Immunohistochemistry and RT-PCR for MCR expression were performed in human meibomian glands and an immortalized human meibomian gland epithelial cell line (ihMGECs). The effects of α-/β-MSH (agonists) and JNJ-10229570 (antagonist) in ihMGECs on lipid production and MCR response were analyzed using Oil-Red-O staining, transmission electron microscopy, qPCR, and a cAMP assay. Additionally, the effect of α-/β-MSH on an ex vivo organotypic slice culture (OSC) of human eyelids was investigated. Results MCR expression was confirmed in human meibomian glands. Stimulation with α-/β-MSH increased cAMP levels and MCR expression. α-/β-MSH dose-dependently induced lipid production in ihMGECs and OSC, resulting in increased lipid droplet formation and upregulation of lipogenesis markers. Co-administration of JNJ-10229570 suppressed this effect. Conclusion Our data show for the first time that human meibomian glands express MCRs and that stimulation/inhibition of MCRs alters cAMP response, MCR expression, and lipogenesis markers, thereby affecting the genesis of meibum. Therefore, α-/β-MSH positively impacts meibum production and should be considered in the context of changes in glandular secretion in MGD and potential treatment
Keywords: Dry eye disease; Meibomian gland; Meibomian gland dysfunction; Melanocortin receptor; Organotypic slice culture; α-MSH; β-MSH

Analyzing the transmission of visible light through electrospun nanofibrous PCL scaffolds - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Helsinki (Finland), 2021, 2021)

Anatomy and physiology of the nasolacrimal ducts - Paulsen, Friedrich; Garreis, Fabian; Schicht, Martin; Bräuer, Lars; Ali, M. J.; Sel, Saadettin (HNO, 2016)
Ophthalmologists and interventional radiologists are not the only professionals for whom diseases of the efferent tear duct system occupy centre stage; this applies also to ENT specialists involving endonasal conservative or surgical treatment. On the basis of current knowledge and taking account of results yielded by own research in recent years and of clinical aspects, we here give an overview of basic knowledge on the anatomy and physiology of the nasolacrimal system. In doing so functional aspects regarding tear transport as well as embryological and pathophysiological issues are integrated.
EVALuna2:34492

A New Organotypic 3D Slice Culture of Mouse Meibomian Glands Reveals Impact of Melanocortins - Zahn, Ingrid; Garreis, Fabian; Schicht, Martin; Rötzer, Vera; Waschke, Jens; Liu, Yuqiuhe; Altersberger, Valerian; Paulsen, Friedrich; Dietrich, Jana (International Journal of Molecular Sciences, 2022)
The meibomian glands (MGs) within the eyelids produce a lipid-rich secretion that forms the superficial layer of the tear film. Meibomian gland dysfunction (MGD) results in excessive evaporation of the tear film, which is the leading cause of dry eye disease (DED). To develop a research model similar to the physiological situation of MGs, we established a new 3D organotypic slice culture (OSC) of mouse MGs (mMGs) and investigated the effects of melanocortins on exocrine secretion. Tissue viability, lipid production and morphological changes were analyzed during a 21-day cultivation period. Subsequently, the effects on lipid production and gene expression were examined after stimulation with a melanocortin receptor (MCR) agonist, α-melanocyte-stimulating hormone (α-MSH), and/or an MCR antagonist, JNJ-10229570. The cultivation of mMGs OSCs was possible without impairment for at least seven days. Stimulation with the MCR agonists induced lipid production in a dose-dependent manner, whereas this effect was tapered with the simultaneous incubation of the MCR antagonist. The new 3D OSC model is a promising approach to study the (patho-) physiological properties of MG/MGD while reducing animal studies. Therefore, it may accelerate the search for new treatments for MGD/DED and lead to new insights, such as that melanocortins likely stimulate meibum production.
CRIS-Team Scopus Importer:2022-12-23
Keywords: 3D cell culture model; dry eye disease; meibomian gland; meibomian gland dysfunction; melanocortin receptor; organotypic slice culture; vibratome; α-MSH

Antimicrobial Peptides as Endogenous Antibacterials and Antivirals at the Ocular Surface - Garreis, Fabian; Schicht, Martin; Paulsen, Friedrich (Springer Basel, 2016)
Ocular surface infections are a significant cause of blindness worldwide particularly in developing countries and are mainly caused by bacteria, fungal species, and parasites as well as by viruses. Staphylococcus epidermidis, Staphylococcus aureus, Streptococcus pneumonia, and Pseudomonas aeruginosa are reported to be the most common bacteria associated with keratitis where the most frequent viruses leading to ocular surface infection are herpes simplex, adenovirus, and vaccinia virus. The eye and its adnexa have evolved a bulk of defense strategies to prevent microbial invasion. These include important components of the innate defense system in form of classical antimicrobial compounds as well as members of the cationic antimicrobial peptide family, distinct surfactant proteins, and potential new candidate molecules contributing to antimicrobial protection. Several of them are studied at the ocular surface not only for their antimicrobial properties, but based on easy topical application possibilities for their potential therapeutic effects. As several reviews already summarized the current knowledge with regard to the eye, this chapter will only briefly recapitulate the current knowledge of antimicrobial compound expression in the eye and then will focus on infectious keratitis resulting from bacterial and viral infection. In addition, the potential of using such peptides as therapeutics for treating bacterial and viral ocular surface infections will be elucidated.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Herpes Simplex Virus Infection; Lacrimal Gland; Ocular Surface; Secretory Leukocyte Protease Inhibitor; Trefoil Factor Family

Assessment of a preclinical dry eye model using ultrahigh-resolution optical coherence tomography - Pfister, Martin; Messner, Alina; Fischak, Corinna; Garreis, Fabian; Paulsen, Friedrich; Schutzenberger, Kornelia; Dos Santos, Valentin Aranha; Stegmann, Hannes; Garhofer, Gerhard; Schmetterer, Leopold; Werkmeister, Rene Marcel (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Autohaemotherapy based on gelsolin (GSN) enrichment supports corneal wound closure and has an anti-inflammatory effect on the ocular surface - Feldt, Jessica; Schicht, Martin; Garreis, Fabian; Welss, Jessica; Schneider, Ulrich; Paulsen, Friedrich (2019)
EVALuna2:210793

Bone marrow cells and CD117-positive haematopoietic stem cells promote corneal wound healing - Sel, Saadettin; Schilling, Ulf M.; Nass, Norbert; Simm, Andreas; Garreis, Fabian; Knak, Matthias; Storsberg, Joachim; Kaiser, Maja; Kalinski, Thomas; Ehrich, Dirk; Bredehorn-Mayr, Timm; Paulsen, Friedrich (Acta Ophthalmologica, 2012)
Purpose: The present study was conducted to evaluate the therapeutic effects of topically applied bone marrow (BM) cells and CD117-positive haematopoietic stem (CD117(+)) cells on alkali-induced corneal ulcers. Methods: Bone marrow cells and CD117(+) cells were isolated from syngenic mice and labelled with an intracellular cell tracer. Defined corneal wounds were produced in 89 eyes of syngenic mice and allowed to partially heal in vivo for 6 hr. The alkali-burned eyes were enucleated 6 hr postinjury and randomly divided into three groups. Control group (33 eyes) was incubated with medium only. The treatment groups received either BM cells (30 eyes) or CD117(+) cells (26 eyes) suspended in medium. Re-epithelialization process of corneal defects was qualitatively and quantitatively assessed and statistically analysed. The corneas were examined by histological and immunohistochemical methods. Results: We found that the re-epithelialization of corneal wounds in both treatment groups was significantly accelerated as compared to the control group. During the follow-up period (85 hr), the corneal transparency was comparable in all groups. Morphological investigations of corneas from control and treatment group showed no evident differences in the phenotype of the regenerated epithelium. Additionally, corneas in the treatment groups were devoid of donor-derived BM cells and CD117(+) cells, respectively. Conclusions: This study provides evidence that topical application of BM cells or CD117(+) cells can be used to reconstruct corneal surfaces. Because neither BM cells nor CD117(+) cells were integrated into the corneal epithelium, we suggest that soluble factors could be responsible for the positive effect of BM cells and CD117(+) cells on corneal wound healing.
EVALuna2:4383

C1q/TNF-Related Proteins 1, 6 and 8 Are Involved in Corneal Epithelial Wound Closure by Targeting Relaxin Receptor RXFP1 In Vitro - Nicolaus, Hagen; Klonisch, Thomas; Paulsen, Friedrich; Garreis, Fabian (International Journal of Molecular Sciences, 2023)
Inadequate wound healing of ocular surface injuries can lead to permanent visual impairment. The relaxin ligand-receptor system has been demonstrated to promote corneal wound healing through increased cell migration and modulation of extracellular matrix formation. Recently, C1q/tumor necrosis factor-related protein (CTRP) 8 was identified as a novel interaction partner of relaxin receptor RXFP1. Additional data also suggest a role for CTRP1 and CTRP6 in RXFP1-mediated cAMP signaling. However, the role of CTRP1, CTRP6 and CTRP8 at the ocular surface remains unclear. In this study, we investigated the effects of CTRP1, CTRP6, and CTRP8 on epithelial ocular surface wound closure and their dependence on the RXFP1 receptor pathway. CTRP1, CTRP6, and CTRP8 expression was analyzed by RT-PCR and immunohistochemistry in human tissues and cell lines derived from the ocular surface and lacrimal apparatus. In vitro ocular surface wound modeling was performed using scratch assays. We analyzed the effects of recombinant CTRP1, CTRP6, and CTRP8 on cell proliferation and migration in human corneal and conjunctival epithelial cell lines. Dependence on RXFP1 signaling was established by inhibiting ligand binding to RXFP1 using a specific anti-RXFP1 antibody. We detected the expression of CTRP1, CTRP6, and CTRP8 in human tissue samples of the cornea, conjunctiva, meibomian gland, efferent tear ducts, and lacrimal gland, as well as in human corneal, conjunctival, and meibomian gland epithelial cell lines. Scratch assays revealed a dose-dependent increase in the closure rate of surface defects in human corneal epithelial cells after treatment with CTRP1, CTRP6, and CTRP8, but not in conjunctival epithelial cells. Inhibition of RXFP1 fully attenuated the effect of CTRP8 on the closure rate of surface defects in human corneal epithelial cells, whereas the CTRP1 and CTRP6 effects were not completely suppressed. Conclusions: Our findings demonstrate a novel role for CTRP1, CTRP6, and CTRP8 in corneal epithelial wound closure and suggest an involvement of the relaxin receptor RXFP1 signaling pathway. This could be a first step toward new approaches for pharmacological and therapeutic intervention.
CRIS-Team Scopus Importer:2023-04-21
Keywords: C1q/TNF-related proteins; C1QTNF; corneal wound closure; CTRP1; CTRP6; CTRP8; lacrimal apparatus; ocular surface; relaxin receptor; RXFP1

Calcium regulation by temperature-sensitive transient receptor potential channels in human uveal melanoma cells - Mergler, Stefan; Derckx, Raissa; Reinach, Peter S.; Garreis, Fabian; Boehm, Anna; Schmelzer, Lisa; Skosyrski, Sergej; Ramesh, Niraja; Abdelmessih, Suzette; Polat, Onur Kerem; Khajavi, Noushafarin; Riechardt, Aline Isabel (Cellular Signalling, 2014)
Uveal melanoma (UM) is both the most common and fatal intraocular cancer among adults worldwide. As with all types of neoplasia, changes in Ca(2+) channel regulation can contribute to the onset and progression of this pathological condition. Transient receptor potential channels (TRPs) and cannabinoid receptor type 1 (CB1) are two different types of Ca(2+) permeation pathways that can be dysregulated during neoplasia. We determined in malignant human UM and healthy uvea and four different UM cell lines whether there is gene and functional expression of TRP subtypes and CB1 since they could serve as drug targets to either prevent or inhibit initiation and progression of UM. RT-PCR, Ca(2+) transients, immunohistochemistry and planar patch-clamp analysis probed for their gene expression and functional activity, respectively. In UM cells, TRPV1 and TRPM8 gene expression was identified. Capsaicin (CAP), menthol or icilin induced Ca(2+) transients as well as changes in ion current behavior characteristic of TRPV1 and TRPM8 expression. Such effects were blocked with either La(3+), capsazepine (CPZ) or BCTC. TRPA1 and CB1 are highly expressed in human uvea, but TRPA1 is not expressed in all UM cell lines. In UM cells, the CB1 agonist, WIN 55,212-2, induced Ca(2+) transients, which were suppressed by La(3+) and CPZ whereas CAP-induced Ca(2+) transients could also be suppressed by CB1 activation. Identification of functional TRPV1, TRPM8, TRPA1 and CB1 expression in these tissues may provide novel drug targets for treatment of this aggressive neoplastic disease.
EVALuna2:4406

Calcium regulation by thermo- and osmosensing transient receptor potential vanilloid channels (TRPVs) in human conjunctival epithelial cells - Mergler, Stefan; Garreis, Fabian; Sahlmueller, Monika; Lyras, Ekaterini-Maria; Reinach, Peter S.; Dwarakanath, Abhilash; Paulsen, Friedrich; Pleyer, Uwe (Histochemistry and Cell Biology, 2012)
Transient receptor potential vanilloid (TRPV) channels respond to polymodal stresses to induce pain, inflammation and tissue fibrosis. In this study, we probed for their functional expression in human conjunctival epithelial (HCjE) cells and ex vivo human conjunctivas. Notably, patients suffering from dry eye syndrome experience the same type of symptomology induced by TRPV channel activation in other ocular tissues. TRPV gene and protein expression were determined by RT-PCR and immunohistochemistry in HCjE cells and human conjunctivas (body donors). The planar patch-clamp technique was used to record nonselective cation channel currents. Ca 2+ transients were monitored in fura-2 loaded cells. Cultivated HCjE cells and human conjunctiva express TRPV1, TRPV2, and TRPV4 mRNA. TRPV1 and TRPV4 localization was identified in human conjunctiva. Whereas the TRPV1 agonist capsaicin (CAP) (5-20 μM) -induced Ca 2+ transients were blocked by capsazepine (CPZ) (10 μM), the TRPV4 activator 4α-PDD (10 μM) -induced Ca 2+ increases were reduced by ruthenium-red (RuR) (20 μM). Different heating (<40°C or>43°C) led to Ca 2+ increases, which were also reduced by RuR. Hypotonic challenges of either 25 or 50% induced Ca 2+ transients and nonselective cation channel currents. In conclusion, conjunctiva express TRPV1, TRPV2, and TRPV4 channels which may provide novel drug targets for dry eye therapeutics. Their usage may have fewer side effects than those currently encountered with less selective drugs. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Dry eye; Human conjunctiva; Intracellular Ca; Planar patch-clamp; TRPV channels

Characterization of dry eye disease in a mouse model by optical coherence tomography and fluorescein staining - Messner, Alina; Fischak, Corinna; Pfister, Martin; Schuetzenberger, Kornelia; Garreis, Fabian; Paulsen, Friedrich; Stegmann, Hannes; Dos Santos, Valentin Aranha; Garhoefer, Gerhard; Schmetterer, Leopold; Werkmeister, Rene M. (Biomedical Optics Express, 2019)
A custom-built ultrahigh-resolution optical coherence tomography (UHR-OCT) system and fluorescein staining were employed tier investigation of a scopolamine induced dry eye mouse model. Acquired data was used to evaluate common and complementary findings of the two modalities. Central corneal thickness as measured by UHR-OCT increased significantly over the study period of 24 hours, from 89.0 +/- 3.57 mu m to 92.2 +/- 4.07 mu m. Both techniques were able to show corneal lesions with a large range of severity. Localized fluorescein staining was detected in 5% and diffuse staining in 45 % of cases where no epithelial damage was visible with OCT. However, OCT revealed stromal defects in 6% and endothelial defects in 18% of the cases, which could not be visualized via fluorescein staining. Thus, while fluorescein staining widely detected defects of the corneal surface in a mouse model of dry eye disease, OCT non-invasively revealed additional intimation about defect depth and involvement of particular layers. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-09-20

Characterization of the innervation of the meibomian glands in humans, rats and mice - Bründl, Maximilian; Garreis, Fabian; Schicht, Martin; Dietrich, Jana; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Aim of the present study was to identify the nerve structures of meibomian glands in humans, rats and mice into sympathetic, parasympathetic and sensory parts as well as their topographical relation with regard to the gland architecture. The upper and lower eyelids of humans, rats and mice were examined by means of immunohistochemistry and indirect immunofluorescence. Specimen were investigated with antibodies against vesicular acetylcholine transporter (VAChT), tyrosine hydroxylase (TH), nitric oxide synthase (NOS), and calcitonin gene-related peptide (CGRP). For overview and general identification of the nervous structures, protein gene product 9.5 (PGP 9.5) was used. PGP-immunoreactive nerve fibers were detectable in the interstitium of the meibomian glands, especially in the neighborhood to the basement membrane of the acini. The axons were positive for CGRP, VAChT, TH and NOS. In addition, the fluorescence labeling also revealed isolated nerve endings surrounding the duct system of the glands, especially along the main duct and in adjacent blood vessels. The density of the innervation of the meibomian glands and the detection of various neuropeptides suggest an influence of the nervous system on the function of the glands. To what extent these may play a role in the modulation of glandular function and the pathogenesis of dry eye disease, or perhaps even represent a possible therapeutic approach, needs further investigation.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Innervation; Meibomian gland; Neurotransmitter; Ocular surface; Tear film

Characterization of the mucocutaneous junction of the human eyelid margin and meibomian glands with different biomarkers - Tektas, Ozan Yüksel; Yadav, Ajay; Garreis, Fabian; Schlötzer-Schrehardt, Ursula; Schicht, Martin; Hampel, Ulrike; Bräuer, Lars; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2012)
To investigate the morphology of the human eyelid margin and the presence of different cytokeratins, mucins and stem cell markers within the skin epithelium, mucocutaneous junction (MCJ) and palpebral conjunctiva.Eyelids of body donors were investigated histologically and ultrastructurally as well as by immunohistochemical methods using antibodies to cytokeratins 1, 4, 7, 8, 10, 13, 14, 15, and 19; mucins MUC1, MUC4, and MUC5AC and potential stem cell markers K15, BCRP/ABCG2, integrin ?1, and N-cadherin.The expression pattern of cytokeratins, mucins and stem cell markers varied across the different epithelia of the human eyelid. Within the MCJ, CK7, 15 and 19 were absent, whereas the epithelium reacted positive to antibodies to CK1, 4, 8, 10, 13 and 14. Reactivity was also observed for MUC1 and MUC4, but not for MUC5AC. No reactivity was determined for K15, BCRP/ABCG2 and integrin ?1 in the area of the MCJ epithelium but a strong reactivity was present for N-cadherin.The present immunohistochemical findings lead to a better characterization of the MCJ. Additionally, the knowledge of distribution of biomarkers like cytokeratins, mucins and stem cells can be useful in the investigation of MCJ disturbances which occur in several disorders of the meibomian glands and the lid epithelium in the course of dry eye syndrome and especially meibomian gland dysfunction.
EVALuna2:4382

Comparative Characterization of Human Meibomian Glands, Free Sebaceous Glands, and Hair-Associated Sebaceous Glands Based on Biomarkers, Analysis of Secretion Composition, and Gland Morphology - Liu, Yuqiuhe; Butovich, Igor A.; Garreis, Fabian; Zahn, Ingrid; Scholz, Michael; Gaffling, Simone; Jabari, Samir; Dietrich, Jana; Paulsen, Friedrich (International Journal of Molecular Sciences, 2024)
Meibomian gland dysfunction (MGD) is one of the main causes of dry eye disease. To better understand the physiological functions of human meibomian glands (MGs), the present study compared MGs with free sebaceous glands (SGs) and hair-associated SGs of humans using morphological, immunohistochemical, and liquid chromatography—mass spectrometry (LCMS)-based lipidomic approaches. Eyelids with MGs, nostrils, lips, and external auditory canals with free SGs, and scalp with hair-associated SGs of body donors were probed with antibodies against cytokeratins (CK) 1, 8, 10, and 14, stem cell markers keratin 15 and N-cadherin, cell–cell contact markers desmoglein 1 (Dsg1), desmocollin 3 (Dsc3), desmoplakin (Dp), plakoglobin (Pg), and E-cadherin, and the tight junction protein claudin 5. In addition, Oil Red O staining (ORO) was performed in cryosections. Secretions of MGs as well as of SGs of nostrils, external auditory canals, and scalps were collected from healthy volunteers, analyzed by LCMS, and the data were processed using various multivariate statistical analysis approaches. Serial sections of MGs, free SGs, and hair-associated SGs were 3D reconstructed and compared. CK1 was expressed differently in hair-associated SGs than in MGs and other free SGs. The expression levels of CK8, CK10, and CK14 in MGs were different from those in hair-associated SGs and other free SGs. KRT15 was expressed differently in hair-associated SGs, whereas N-cadherin was expressed equally in all types of glands. The cell–cell contact markers Dsg1, Dp, Dsc3, Pg, and E-cadherin revealed no differences. ORO staining showed that lipids in MGs were more highly dispersed and had larger lipid droplets than lipids in other free SGs. Hair-associated SGs had a smaller number of lipid droplets. LCMS revealed that the lipid composition of meibum was distinctively different from that of the sebum of the nostrils, external auditory canals, and scalp. The 3D reconstructions of the different glands revealed different morphologies of the SGs compared with MGs which are by far the largest type of glands. In humans, MGs differ in their morphology and secretory composition and show major differences from free and hair-associated SGs. The composition of meibum differs significantly from that of sebum from free SGs and from hair-associated SGs. Therefore, the MG can be considered as a highly specialized type of holocrine gland that exhibits all the histological characteristics of SGs, but is significantly different from them in terms of morphology and lipid composition.
CRIS-Team Scopus Importer:2024-04-05
Keywords: cell–cell contacts; cytokeratins; dry eye disease; meibomian gland dysfunction; meibomian glands; meibum; sebaceous glands; sebum; stem cell markers

DAPK loss in colon cancer tumor buds: implications for migration capacity of disseminating tumor cells - Ivanovska, Jelena; Zlobec, Inti; Forster, Stefan; Karamitopoulou, Eva; Dawson, Heather; Koelzer, Viktor Hendrik; Agaimy, Abbas; Garreis, Fabian; Söder, Stephan; Laqua, William; Lugli, Alessandro; Hartmann, Arndt; et al. (Oncotarget, 2015)
Defining new therapeutic strategies to overcome therapy resistance due to tumor heterogeneity in colon cancer is challenging. One option is to explore the molecular profile of aggressive disseminating tumor cells. The cytoskeleton-associated Death-associated protein kinase (DAPK) is involved in the cross talk between tumor and immune cells at the invasion front of colorectal cancer. Here dedifferentiated tumor cells histologically defined as tumor budding are associated with a high risk of metastasis and poor prognosis. Analyzing samples from 144 colorectal cancer patients we investigated immunhistochemical DAPK expression in different tumor regions such as center, invasion front, and buds. Functional consequences for tumor aggressiveness were studied in a panel of colon tumor cell lines using different migration, wound healing, and invasion assays. DAPK levels were experimentally modified by siRNA transfection and overexpression as well as inhibitor treatments. We found that DAPK expression was reduced towards the invasion front and was nearly absent in tumor buds. Applying the ECIS system with HCT116 and HCT116 stable lentiviral DAPK knock down cells (HCTshDAPK) we identified an important role for DAPK in decreasing the migratory capacity whereas proliferation was not affected. Furthermore, the migration pattern differed with HCTshDAPK cells showing a cluster-like migration of tumor cell groups. DAPK inhibitor treatment revealed that the migration rate was independent of DAPK's catalytic activity. Modulation of DAPK expression level in SW480 and DLD1 colorectal cancer cells significantly influenced wound closure rate. DAPK seems to be a major player that influences the migratory capability of disseminating tumor cells and possibly affects the dynamic interface between pro- and anti-survival factors at the invasion front of colorectal cancer. This interesting and new finding requires further evaluation.
EVALuna2:4438

Developmental change in the gene-expression of transient receptor potential melanostatin channel 3 (TRPM3) in murine lacrimal gland - Kanewska, Anna; Ito, Masataka; Karasawa, Yoko; Inada, Makoto; Garreis, Fabian; Paulsen, Friedrich; Takeuchi, Masaru (2018)
EVALuna2:35312

Developmental change in the gene expression of transient receptor potential melastatin channel 3 (TRPM3) in murine lacrimal gland - Kanewska, A.; Ito, M.; Karasawa, Y.; Inada, M.; Garreis, Fabian; Paulsen, Friedrich; Takeuchi, M. (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Transient receptor potential (TRP) channels are cation channels with ubiquitous expression. Various TRP channels are functionally active at the ocular surface and are involved in tear secretion and multiple inflammatory processes. So far, the impact of TRP channels regarding the development of the lacrimal gland (LG) is unclear. While investigating TRP channels in the LG, the TRPM3 channel presented itself as a promising candidate to play a role in the development and functioning of the LG. Therefore, Trpm3 expression was analyzed in different embryonic and postembryonic LGs. Thus, gene expression of TRPM channels including Trpm2, Trpm3, Trpm4 and Trpm6 was analyzed by quantitative RT-PCR in murine LGs at different developmental stages. Localization of TRPM3 in LGs was examined by immunohistochemistry. Primary LG epithelial cells (LGEC) and mesenchymal cells (MC) from newborn mice were cultured (either separately or collectively) for three days, and Trpm3 expression was analyzed in LGEC and MC. As a result, gene expression of Trpm2, Trpm4 and Trpm6 showed no significant difference in LGs in the different stages of development. However, Trpm3 gene expression was significantly higher in the embryonic stage than in the postnatal stage with the peak at E18. Postnatal, Trpm3 expression significantly decreased up to 28-fold until two years of age. Immunohistochemistry for TRPM3 revealed apical membranous expression in the excretory ducts, as well as in the acini of up to P7 old mice. Trpm3 expression in LGEC were significantly higher than that of MC. Our results indicate that Trpm3 expression in murine LG is age-dependent and peaks at age E18. Its expression is localized in the apical membrane of the glandular epithelium. However, its functional role still requires additional study in the LG.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Development; Lacrimal gland; Ocular surface; Ophthalmology; TRP channels

Differentiation Patterns of Immortalized Human Meibomian Gland Epithelial Cells in Three-Dimensional Culture - Asano, Nagayoshi; Hampel, Ulrike; Garreis, Fabian; Schröder, Antje; Schicht, Martin; Hammer, Christian; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2018)
Purpose: To establish a simplified three-dimensional (3D) meibomian gland culture model using a meibomian gland epithelial cell (HMGEC) line that might be a useful tool to gain deeper insights into meibomian gland dysfunction. For this purpose, 3D differentiation patterns and growth characteristics of HMGECs were studied on various membranes/scaffolds as well as in hanging drops. Methods: Several types of inserts consisting of different materials (Millicell-HA, Millicell-PCF, ThinCert, and Alvetex) as well as hanging drop culture were analyzed. Culture conditions were optimized employing exposure to air (air-lift) and different cell culture media for a maximum of 28 days. To characterize cell differentiation in the developed 3D model, the expression pattern of cytokeratins was investigated by immunohistochemistry. Sudan III staining was performed for detection of lipid formation and transmission electron microscopy (TEM) was used for ultrastructural analysis. Results: Only Alvetex scaffolds and the hanging drop method revealed satisfactory results with regard to 3D culture. Continuous use of proliferation medium (serum-free keratinocyte medium containing epidermal growth factor and bovine pituitary extract) and air-lift were important steps for HMGEC differentiation in 3D culture. However, HMGECs only reached a differentiating state and never became mature or hypermature. When cultured in hanging drops, HMGECs showed serum-induced keratinization processes. Conclusions: HMGECs have the capability to differentiate in a long-term 3D culture, especially when adapted to an air-rich environment. However, even in the 3D format, HMGECs only reach a state of differentiating meibocytes.
EVALuna2:35318

E-Cadherin Is Important for Meibomian Gland Function as Revealed by a New Human ex Vivo Slice Culture Model - Rötzer, Vera; Melega, Francesca; Garreis, Fabian; Paulsen, Friedrich; Waschke, Jens (American Journal of Pathology, 2019)
Meibomian glands within the eyelid are important for the maintenance of the integrity and health of the ocular surface. Patients with the blistering skin disease pemphigus vulgaris (PV), which is caused by autoantibodies against desmosomal cadherins, often have dry eye disease. Therefore, we studied the regulation of cell cohesion in human meibomian gland epithelial cells (HMGECs). During serum-induced differentiation for 1 to 6 days, HMGECs drastically enhanced intercellular cohesion, whereas lipid production did not change. The expression profiles of the desmosomal PV antigens desmoglein (Dsg) 3 and 1 but not of the adherens junction component E-cadherin (Ecad) was dependent on the presence of serum. Surprisingly, after 1 day but not after 6 days of serum-induced differentiation, an inhibitory antibody against Ecad drastically reduced intercellular cohesion and blocked lipid production of HMGECs. In contrast, antibodies against desmosomal cadherins, including human and mouse pemphigus autoantibodies, had no effect on monolayer integrity and lipid production. Because lipid production was unaltered in meibomian glands from Dsg3-deficient mice, we established an ex vivo slice culture model of human eyelids to allow studies in a more physiologic environment. Here, the inhibitory antibody against Ecad but not a Dsg3-specific PV antibody interfered with stimulated lipid production. Together, these data demonstrate that cell cohesion is maintained differently in meibomian gland cells and indicate that Ecad is important for meibomian gland function.
CRIS-Team Scopus Importer:2019-08-02

Effect of intermittent shear stress on corneal epithelial cells using an in vitro flow culture model - Hampel, Ulrike; Garreis, Fabian; Burgemeister, Fabian; Eßel, Nicole; Paulsen, Friedrich (Ocular Surface, 2018)
PURPOSE: The aim of this study was to establish and to evaluate an in vitro model for culturing human telomerase-immortalized corneal epithelial (hTCEpi) cells under adjustable medium flow mimicking the movements of the tear film on the ocular surface. METHODS: Using an IBIDI pump system, cells were cultured under unidirectional, continuous or oscillating, discontinuous medium flow. Cell surface and cytoskeletal architecture were investigated by scanning electron microscopy and immunofluorescence. Gene expression of e-cadherin, occludin, tight junction protein (TJP), desmoplakin, desmocollin and mucins was investigated by real-time PCR. Protein expression of desmoplakin, TJP, occludin and e-cadherin was analyzed by western blot and localization was detected by immunofluorescence. Rose bengal staining was used to assess mucin (MUC) barrier integrity. MUC1, -4 and -16 proteins were localized by immunofluorescence. RESULTS: Medium flow-induced shear stress dramatically changed cellular morphology of hTCEpi. Cells subjected to discontinuous shear stress displayed the typical flattened, polygonal cell shape of the superficial layer of stratified squamous epithelia. Cell surfaces showed less bulging under shear stress and less extracellular gaps. The mRNA expression of E-cadherin, occludin and TJP were increased under oscillatory medium flow. Desmoplakin and occludin protein were upregulated under oscillatory shear stress. Stress fiber formation was not aligned to flow direction. MUC1, -4, and -16 protein were localized under all culture conditions, a regulation on mRNA expression was not detectable. Rose Bengal uptake was diminished under unidirectional conditions. CONCLUSION: Our findings suggest that shear stress as it occurs at the ocular surface during blinking exerts marked effects on corneal epithelial cells, such as changes in cellular morphology and expression of cell junctions. The described model may be useful for in vitro investigations of ocular surface epithelia as it represents a much more physiologic reproduction of the in vivo situation than the commonly applied static culture conditions.
EVALuna2:35314

Efficacy of aflibercept (EYLEA®) on inhibition of human VEGF in vitro - Schicht, Martin; Hesse, Karen; Schröder, Henrik; Naschberger, Elisabeth; Lamprecht, W.; Garreis, Fabian; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Pathological formation of blood vessels plays a key role in the growth and metastasis of tumors and also in several serious ophthalmological diseases such as wet age-related macular degeneration (AMD) or diabetic retinopathy. In AMD treatment, aflibercept (tradename EYLEA®) is used to deactivate the underlying pathological neovascularisation. Aflibercept is a recombinant fusion protein which binds to vascular endothelial growth factor (VEGF) receptors, thereby inhibiting VEGF pathway activation. VEGF is one of the most important angiogenesis factors.This analysis investigates lasting efficacy of aflibercept in vitro for later application as therapeutic agent against macular degeneration (AMD).VEGF-ELISA assays were performed to investigate binding affinities at different aflibercept concentrations. The impact of VEGF on the proliferation of human umbilical vein endothelial cells (HUVEC) was investigated using proliferation assays. Moreover, time-dependent kinetic studies were performed to analyze different aflibercept storage durations with regard to its inhibitory capabilities on human VEGF.Our results reveal that aflibercept significantly lowers the amount of unbound VEGF as well as the proliferation rate of HUVEC. Moreover, in contrast to specifications given by the manufacturer, aflibercept retains its full inhibitory effect up to at least 120h after transference from the original vial into the injection syringe.
EVALuna2:15305
Keywords: Aflibercept; VEGF; VEGF-trap; EYLEA®; HUVEC

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (16th Biennial - Bayreuther Polymer Symposium, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (30th Annual Conference of the European Society for Biomaterials, Dresden (Deutschland), 2019, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (16th Bayreuther Polymer Symposium, Bayreuth (Deutschland), 2019., 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Trondheim (Norwegen), 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (The Association for Research in Vision and Ophthalmology (ARVO), 2019)

Evaluation of surfactant proteins A, B, C, and D in articular cartilage, synovial membrane and synovial fluid of healthy as well as patients with osteoarthritis and rheumatoid arthritis - Hartjen, Nadine; Bräuer, Lars; Reiss, Beate; Claassen, Horst; Beileke, Stephanie; Garreis, Fabian; Hoogeboom, Sebastian; Tsokos, Michael; Etzold, Saskia; Mueller-Hilke, Brigitte; Gelse, Kolja; Mueller, Thomas; et al. (PLoS ONE, 2018)
OBJECTIVE: Surfactant Proteins (SPs) are well known from lung and form, along with phospholipids, a surface-active-layer at the liquid-air-interface of the alveolar lining. They play a major protective role by lowering surface tension, activating innate and adaptive immune defense at the lung mucosal interface, especially during infection. We analyzed the regulation of SPs in human and mouse articular chondrocytes, synoviocytes, and synovial fluid under healthy and inflammatory conditions, as well as in tissues of patients suffering from osteoarthritis and rheumatoid arthritis. METHODS: Immunohistochemistry, RT-PCR, qRT-PCR, ELISA, Western blotting were performed in cell cultures and tissue samples to determine localization, regulation, and concentration of SPs. RESULTS: All four SPs, were expressed by healthy human and mouse articular chondrocytes and synoviocytes and were also present in synovial fluid. Treatment with inflammatory mediators like IL-1β and TNF-α led to short-term upregulation of individual SPs in vitro. In tissues from patients with osteoarthritis and rheumatoid arthritis, protein levels of all four SPs increased significantly compared to the controls used. CONCLUSION: These results show the distribution and amount of SPs in tissues of articular joints. They are produced by chondrocytes and synoviocytes and occur in measurable amounts in synovial fluid. All four SPs seem to be differently regulated under pathologic conditions. Their physiological functions in lowering surface tension and immune defense need further elucidation and make them potential candidates for therapeutic intervention.
EVALuna2:35305

Expression and Localization of Lung Surfactant Proteins in Human Testis - Beileke, Stephanie; Claassen, Horst; Wagner, Walter; Matthies, Cord; Ruf, Christian; Hartmann, Arndt; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (PLoS ONE, 2015)
Surfactant proteins (SPs) have been described in various tissues and fluids including tissues of the nasolacrimal apparatus, airways and digestive tract. Human testis have a glandular function as a part of the reproductive and the endocrine system, but no data are available on SPs in human testis and prostate under healthy and pathologic conditions.The aim of the study was the detection and characterization of the surfactant proteins A, B, C and D (SP-A, SP-B, SP-C, SP-D) in human testis. Additionally tissue samples affected by testicular cancer were investigated.Surfactant proteins A, B, C and D were detected using RT-PCR in healthy testis. By means of Western blot analysis, these SPs were detected at the protein level in normal testis, seminoma and seminal fluid, but not in spermatozoa. Expression of SPs was weaker in seminoma compared to normal testicular tissue. SPs were localized in combination with vimentin immunohistochemically in cells of Sertoli and Leydig.Surfactant proteins seem to be inherent part of the human testis. By means of physicochemical properties the proteins appear to play a role during immunological and rheological process of the testicular tissue. The presence of SP-B and SP-C in cells of Sertoli correlates with their function of fluid secretion and may support transportation of spermatozoa. In seminoma the expression of all SP's was generally weaker compared to normal germ cells. This could lead to a reduction of immunomodulatory and rheology processes in the germ cell tumor.
EVALuna2:4444

Expression and Regulation of S100 Fused-Type Protein Hornerin at the Ocular Surface and Lacrimal Apparatus - Garreis, Fabian; Jahn, Janine; Wild, Katharina; Abrar, Daniel; Schicht, Martin; Schroeder, Jens-Michael; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2017)
Purpose: The S100 fused-type proteins hornerin (HRNR) and filaggrin-2 (FLG2) are members of the epidermal differentiation complex, which is involved in terminal differentiation of keratinocytes via cornification as well as maintenance of the epidermal antimicrobial barrier. We investigated the expression and possible regulation of HRNR and FLG2 at the ocular surface and in the lacrimal apparatus. Methods: Tissues of the lacrimal apparatus and ocular surface were analyzed systematically by means of RT-PCR, immunohistochemistry, and immuntransmission electron microscopy (iTEM) for their ability to express and produce HRNR and FLG2. In addition, inducibility and regulation of HRNR were studied in cultivated human corneal (HCE), conjunctival (HCjE), as well as meibomian gland (HMGEC) epithelial cell line by real-time RT-PCR. Results: RT-PCR, immunohistochemistry, and iTEM revealed constitutive expression of HRNR in the epithelium of cornea, conjunctiva, nasolacrimal ducts, and acinus cells of lacrimal and meibomian glands. HRNR also was detected in tears of healthy volunteers. No expression of FLG2 could be detected in tissue samples of the ocular surface and lacrimal apparatus. Real-time RT-PCR revealed a decreased HRNR gene expression after challenge with proinflammatory cytokines and supernatants of Escherichia coli and Pseudomonas aeroginosa in HCE cells, whereas HCjE cells revealed no changes. In HMGECs serum-induced differentiation and application of all-trans retinoic acid significantly increased HRNR gene expression. Conclusions: The data suggest that HRNR, but not FLG2, is a component of the ocular surface and lacrimal apparatus, including meibomian glands. HRNR seems to contribute to the maintenance of the epithelial barrier at the ocular surface and, thus, also may be involved in ocular surface diseases.
EVALuna2:35323

Functional Protective Effects of Long-Term Memantine Treatment in the DBA/2J Mouse. - Atorf, Jenny; Scholz, Michael; Garreis, Fabian; Lehmann, Julia; Bräuer, Lars; Kremers, Jan (Documenta Ophthalmologica, 2013)
Purpose: To analyse the effects of long-term memantine treatment on the retinal physiology and morphology of DBA/2J mice. Methods: DBA/2J (D2J) mice received i.p. injections of the NMDA receptor antagonist memantine, which protects neurons from abnormally elevated glutamate levels, twice a day over a period of 7 months. At the age of 2, 6 and 10 months, the intraocular pressure (IOP) and electroretinograms (ERGs) were measured in all treated D2J mice, in untreated D2J controls and in C57Bl/6 (B6) wild-type mice. After the last measurement at the age of 10 months, the mice were killed and the retinae and the optic nerves were analysed morphologically. Results: The IOP increased with age in both D2J and B6 mice with a larger increase in the D2J strain. IOPs were not influenced by memantine treatment. The response amplitude of the scotopic flash ERG decreased with age in the D2J strain. This amplitude decrease, particularly that of the b-wave, was smaller in treated D2J mice. The retinae of treated D2J mice exhibited less peripheral degeneration of cone photoreceptors, and optic nerve neuropathy was less frequent. Conlcusions: Application of the NMDA receptor antagonist memantine diminished retinal neurodegeneration in the D2J mice and had a protective effect on the b-wave amplitude of the scotopic flash ERG. This protection may occur secondarily as memantine primarily acts on retinal ganglion cells. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.med.AI.LAIPDL.functi
Keywords: DBA/2J mouse; Electroretinography; Memantine; Neurodegeneration

Human synovia contains trefoil factor family (TFF) peptides 1-3 although synovial membrane only produces TFF3: Implications in osteoarthritis and rheumatoid arthritis - Popp, Judith; Schicht, Martin; Garreis, Fabian; Klinger, Patricia; Gelse, Kolja; Sesselmann, Stefan; Tsokos, Michael; Etzold, Saskia; Stiller, Dankwart; Claassen, Horst; Paulsen, Friedrich (International Journal of Molecular Sciences, 2019)
Objective: Trefoil factor family peptide 3 (TFF3) has been shown to support catabolic functions in cases of osteoarthritis (OA). As in joint physiology and diseases such as OA, the synovial membrane (SM) of the joint capsule also plays a central role. We analyze the ability of SM to produce TFF compare healthy SM and its secretion product synovial fluid (SF) with SM and SF from patients suffering from OA or rheumatoid arthritis (RA). Methods: Real-time PCR and ELISA were used to measure the expression of TFFs in healthy SM and SM from patients suffering from OA or RA. For tissue localization, we investigated TFF1-3 in differently aged human SM of healthy donors by means of immunohistochemistry, real-time PCR and Western blot. Results: Only TFF3 but not TFF1 and -2 was expressed in SM from healthy donors as well as cases of OA or RA on protein and mRNA level. In contrast, all three TFFs were detected in all samples of SF on the protein level. No significant changes were observed for TFF1 at all. TFF2 was significantly upregulated in RA samples in comparison to OA samples. TFF3 protein was significantly downregulated in OA samples in comparison to healthy samples and cases of RA significantly upregulated compared to OA. In contrast, in SM TFF3 protein was not significantly regulated. Conclusion: The data demonstrate the production of TFF3 in SM. Unexpectedly, SF contains all three known TFF peptides. As neither articular cartilage nor SM produce TFF1 and TFF2, we speculate that these originate with high probability from blood serum.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Osteoarthritis (OA); Rheumatoid arthritis (RA); Synovial fluid (SF); Synovial membrane (SM); Trefoil factor family peptides (TFF)

IgA subclasses have different effector functions associated with distinct glycosylation profiles - Steffen, Ulrike; Koeleman, Carolien A.; Sokolova, Maria V.; Bang, Holger; Kleyer, Arnd; Rech, Jürgen; Unterweger, Harald; Schicht, Martin; Garreis, Fabian; Hahn, Jonas; Andes, Fabian T.; Hahn, Madelaine; et al. (Nature Communications, 2020)
Monomeric serum immunoglobulin A (IgA) can contribute to the development of various autoimmune diseases, but the regulation of serum IgA effector functions is not well defined. Here, we show that the two IgA subclasses (IgA1 and IgA2) differ in their effect on immune cells due to distinct binding and signaling properties. Whereas IgA2 acts pro-inflammatory on neutrophils and macrophages, IgA1 does not have pronounced effects. Moreover, IgA1 and IgA2 have different glycosylation profiles, with IgA1 possessing more sialic acid than IgA2. Removal of sialic acid increases the pro-inflammatory capacity of IgA1, making it comparable to IgA2. Of note, disease-specific autoantibodies in patients with rheumatoid arthritis display a shift toward the pro-inflammatory IgA2 subclass, which is associated with higher disease activity. Taken together, these data demonstrate that IgA effector functions depend on subclass and glycosylation, and that disturbances in subclass balance are associated with autoimmune disease.
CRIS-Team Scopus Importer:2020-01-21

Impact of prolactin and prolactin-inducible protein (PIP) for dry eye disease - Juengert, Katharina; Paulsen, Friedrich; Garreis, Fabian (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Influence of psoriasin on VEGF-mediated corneal neovascularization - Garreis, Fabian; Beckenbauer, Eva; Schulte, Ulrike; Schicht, Martin; Hampel, Ulrike; Paulsen, Friedrich (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

In vitro effects of docosahexaenoic and eicosapentaenoic acid on human meibomian gland epithelial cells - Hampel, Ulrike; Krüger, Magret; Kunnen, Carolina; Garreis, Fabian; Willcox, Mark; Paulsen, Friedrich (Experimental Eye Research, 2015)
To investigate the effect of ?-3 fatty acids on human meibomian gland epithelial cells (HMGECs, cell line) in vitro. HMGECs were stimulated with docosahexaenoic acid (DHA) or combinations with eicosapentaenoic acid (EPA) and acetyl sialic acid (ASA). Sudan III fat staining, viability and proliferation assays, electric cell-substrate impedance sensing, real-time PCR for gene expression of cyclooxygenase-2 and 15-lipoxygenase and ELISAs for resolvin D1 (RvD1), IFN?, TNF? and IL-6 were applied. Lipid droplet accumulation and viability was increased by 100 ?M DHA in the presence or absence of EPA in serum cultured HMGECs. In contrast, HMGECs cultured with DHA and EPA under serum-free conditions showed minimal lipid accumulation, decreased proliferation and viability. Normalized impedance was significantly reduced in serum-free cultured HMGECs when stimulated with DHA and EPA. HMGECs cultured in serum containing medium showed increased normalized impedance under DHA and EPA stimulation compared to DHA or EPA alone or controls. IL-6 and IFN? were downregulated in HMGECs treated for 72 h with DHA and EPA. In general, TNF?, IFN? and IL-6 levels were decreased after 72 h compared to 24 h in serum containing medium with or without DHA or EPA. The concentration of RvD1 was elevated 2-fold after DHA treatment. Cyclooxygenase-2 gene expression decreased compared to controls during DHA stimulation after 72 h. Treatment with DHA and ASA revealed a decreased 15-lipoxygenase gene expression which was reduced after three days of DHA incubation. DHA and EPA supplementation affected HMGECs in vitro and supported anti-inflammatory effects by influencing cytokine levels, decreasing COX-2 expression and increasing the production of RvD1.
EVALuna2:4441

In vitro effects of sex hormones in human meibomian gland epithelial cells - Schröder, Antje; Abrar, Daniel; Hampel, Ulrike; Schicht, Martin; Paulsen, Friedrich; Garreis, Fabian (Experimental Eye Research, 2016)
Meibomian gland dysfunction (MGD) is considered the most common cause of dry eye disease (DED). Sex hormones seem to play a role in the pathogenesis of MGD although their involvement is not completely understood. Therefore, in the present study we evaluated the effect of dihydrotestosteron (DHT) and estradiol (β-Est) on an immortalized human meibomian gland epithelial cell line (HMGEC). Protein expression of sex hormone receptors in HMGEC was investigated by western blot. Ultrastructural morphology, Sudan III lipid staining, cell proliferation as well as vitality assays were performed. Furthermore, expression of MGD-associated markers for keratinization (hornerin, involucrin and CK6), proliferation (CK5 and CK14) and lipid synthesis (fatty acid synthase and stearoyl-CoA desaturase) were analyzed by real time RT-PCR. Western blot revealed presence of androgen receptor (AR), estrogen receptors α and -β (ERα, ERβ) and progesterone receptor (PR) in HMGEC. PR, ERα and ERβ expression was significantly induced under cultivation with serum, whereas sex hormones stimulation showed no further effect on protein expression of PR, ERα and ERβ. Our results showed no impact of MGD-associated sex hormones to cellular morphology and lipid accumulation in HMGEC. Cell proliferation was slightly induced through application of sex hormones and supplementation of calcium. However, both sex hormones and calcium altered gene expression of MGD-associated markers. Especially keratinization genes hornerin (HRNR) and cornulin (COR) were induced after application of sex hormones and calcium in serum-free cultivated HMGEC. This may promote keratinization processes that are associated with MGD. Further investigations are necessary to analyze the (hyper)keratinization processes that occur during MGD and using HMGEC as an in vitro model.
EVALuna2:35345

Involvement of catecholaminergic neurons in motor innervation of striated muscle in the mouse esophagus - van der Keylen, Piet; Garreis, Fabian; Steigleder, Ruth; Sommer, Daniel; Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2016)
Enteric co-innervation is a peculiar innervation pattern of striated esophageal musculature. Both anatomical and functional data on enteric co-innervation related to various transmitters have been collected in different species, although its function remains enigmatic. However, it is unclear whether catecholaminergic components are involved in such a co-innervation. Thus, we examined to identify catecholaminergic neuronal elements and clarify their relationship to other innervation components in the esophagus, using immunohistochemistry with antibodies against tyrosine hydroxylase (TH), vesicular acetylcholine transporter (VAChT), choline acetyltransferase (ChAT) and protein gene product 9.5 (PGP 9.5), α-bungarotoxin (α-BT) and PCR with primers for amplification of cDNA encoding TH and dopamine-β-hydroxylase (DBH). TH-positive nerve fibers were abundant throughout the myenteric plexus and localized on about 14% of α-BT-labelled motor endplates differing from VAChT-positive vagal nerve terminals. TH-positive perikarya represented a subpopulation of only about 2.8% of all PGP 9.5-positive myenteric neurons. Analysis of mRNA showed both TH and DBH transcripts in the mouse esophagus. As ChAT-positive neurons in the compact formation of the nucleus ambiguus were negative for TH, the TH-positive nerve varicosities on motor endplates are presumably of enteric origin, although a sympathetic origin cannot be excluded. In the medulla oblongata, the cholinergic ambiguus neurons were densely supplied with TH-positive varicosities. Thus, catecholamines may modulate vagal motor innervation of esophageal-striated muscles not only at the peripheral level via enteric co-innervation but also at the central level via projections to the nucleus ambiguus. As Parkinson's disease, with a loss of central dopaminergic neurons, also affects the enteric nervous system and dysphagia is prevalent in patients with this disease, investigation of intrinsic catecholamines in the esophagus may be worthwhile to understand such a symptom.
EVALuna2:35349

Molecular detection of lacrimal apparatus and ocular surface - related ABC transporter genes - Kleinsasser, Benedikt; Garreis, Fabian; Musialik, Maximilian; Zahn, Ingrid; Kral, Barbara; Kutlu, Zeynep; Sahin, Afsun; Paulsen, Friedrich; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2024)
The ocular system is in constant interaction with the environment and with numerous pathogens. The ATP-binding cassette (ABC) transporters represent one of the largest groups among the transmembrane proteins. Their relevance has been demonstrated for their defense function against biotic and abiotic stress factors, for metabolic processes in tumors and for their importance in the development of resistance to drugs. The aim of this study was to analyze which ABC transporters are expressed at the ocular surface and in the human lacrimal apparatus. Using RT-PCR, all ABC transporters known to date in humans were examined in tissue samples from human cornea, conjunctiva, meibomian glands and lacrimal glands. The RT-PCR analyses revealed the presence of all ABC transporters in the samples examined, although the results for some of the 48 transporters known in human and analyzed were different in the various tissues. The present results provide information on the expression of ABC transporters at the mRNA level on the ocular surface and in the lacrimal system. Their detection forms the basis for follow-up studies at the protein level, which will provide more information about their physiological significance at the ocular surface and in the lacrimal system and which may explain pathological effects such as drug resistance.
CRIS-Team Scopus Importer:2024-05-17
Keywords: ABC transporter; Cornea; Eye; Lacrimal gland; Meibomian gland; Ocular surface

Morphological Features of the Porcine Lacrimal Gland and Its Compatibility for Human Lacrimal Gland Xenografting - Henker, Robert; Scholz, Michael; Gaffling, Simone; Nagayoshi, Asano; Hampel, Ulrike; Garreis, Fabian; Hornegger, Joachim; Paulsen, Friedrich (PLoS ONE, 2013)

Ocular Phenotype of Relaxin Gene Knockout (Rln-/-) Mice - Hampel, Ulrike; Chinnery, Holly R.; Garreis, Fabian; Paulsen, Friedrich; de Iongh, Robb; Bui, Bang V.; Nguyen, Christine; Parry, Laura; Chen, Huei Leo (Current Eye Research, 2020)
Purpose: To test if relaxin deficiency affects ocular structure and function we investigated expression of relaxin (Rln) and RXFP receptors (Rxfp1, Rxfp2), and compared ocular phenotypes in relaxin gene knockout (Rln−/−) and wild type (Rln+/+) mice. Materials and Methods: Rln, Rxfp1 and Rxfp2 mRNA expression was detected in ocular tissues of Rln+/+ mice using RT-PCR. The eyes of 11 Rln−/− and 5 Rln+/+ male mice were investigated. Corneal and retinal thickness was assessed using optical coherence tomography. Intraocular pressure was measured using a rebound tonometer. Retinal, choroidal and sclera morphology and thickness were evaluated histologically. Eyes were collected and fixed for immunofluorescence staining or used for RNA extraction to evaluate mRNA expression using real-time PCR. Results: Rln mRNA was expressed only in the retina, whereas Rxfp1 transcripts were detected in the retina, cornea and sclera/choroid. Rxfp2 was only present in the cornea. None of these genes were expressed in the lacrimal gland, eyelid or lens. Intraocular pressure was higher and central cornea of Rln−/− mice was significantly thicker and had significantly larger endothelial cells and a lower endothelial cell density than Rln+/+ mice. Immunohistochemistry demonstrated no significant difference in AQP3 and AQP5 staining in the cornea or other regions between wildtype and Rln−/− mice. mRNA expression of Aqp4 was significantly higher in Rln−/− than in Rln+/+ corneas, whereas Col1a2, Mmp9, Timp1 and Timp2 were significantly decreased. Expression of Aqp1, Aqp4, Aqp5, Vim and Tjp1 was significantly decreased in Rln−/− compared to Rln+/+ uvea. No significant differences in these genes were detected in the retina. Retinal, choroidal and scleral thicknesses were not different and morphology appeared normal. Conclusion: The findings indicate that loss of Rln affects expression of several genes in the uvea and cornea and results in thicker corneas with altered endothelial cells. Many of the gene changes suggest alterations in extracellular matrix and fluid transport between cells.
CRIS-Team Scopus Importer:2020-03-27
Keywords: corneal thickness; phenotype eye; Relaxin knockout

Optimization of polycaprolactone‑ based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Nature Medicine, 2021)
Posterior lamellar transplantation of the eye’ s cornea (DSAEK, DMEK) currently is the gold standard for treating patients with corneal endothelial cell and back surface pathologies resulting in functional impairment. An artificial biomimetic graft carrying human corneal endothelium could minimize the dependency on human donor corneas giving access to this vision‑restoring surgery to large numbers of patients, thus reducing current long waiting lists. In this study, four groups of electrospun nanofibrous scaffolds were compared: polycaprolactone (PCL), PCL/collagen, PCL/gelatin and PCL/chitosan. Each of the scaffolds were tissue‑engineered with human corneal endothelial cells (HCEC‑B4G12) and analyzed with regard to their potential application as artificial posterior lamellar grafts. Staining with ZO‑1 and Na+/K+‑ATPase antibodies revealed intact cell functionalities. It could be shown, that blending leads to decreasing contact angle, whereby a heterogeneous blend morphology could be revealed. Scaffold cytocompatibility could be confirmed for all groups via live/dead staining, whereby a significant higher cell viability could be observed for the collagen and gelatine blended matrices with 97 ± 3% and 98 ± 2% living cells respectively. TEM images show the superficial anchoring of the HCECs onto the scaffolds. This work emphasizes the benefit of blended PCL nanofibrous scaffolds for corneal endothelial keratoplast

Optimization of polycaprolactone - based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Scientific Reports, 2021)

Osteopontin is induced by TGF-?2 and regulates metabolic cell activity in cultured human optic nerve head astrocytes - Neumann, Carolin; Garreis, Fabian; Paulsen, Friedrich; Hammer, Christian; Birke, Marco T.; Scholz, Michael (PLoS ONE, 2014)
The aqueous humor (AH) component transforming growth factor (TGF)-?2 is strongly correlated to primary open-angle glaucoma (POAG), and was shown to up-regulate glaucoma-associated extracellular matrix (ECM) components, members of the ECM degradation system and heat shock proteins (HSP) in primary ocular cells. Here we present osteopontin (OPN) as a new TGF-?2 responsive factor in cultured human optic nerve head (ONH) astrocytes. Activation was initially demonstrated by Oligo GEArray microarray and confirmed by semiquantitative (sq) RT-PCR, realtime RT-PCR and western blot. Expressions of most prevalent OPN receptors CD44 and integrin receptor subunits ?V, ?4, ? 5, ?6, ?9, ?1, ?3 and ?5 by ONH astrocytes were shown by sqRT-PCR and immunofluorescence labeling. TGF-?2 treatment did not affect their expression levels. OPN did not regulate gene expression of described TGF-?2 targets shown by sqRT-PCR. In MTS-assays, OPN had a time- and dose-dependent stimulating effect on the metabolic activity of ONH astrocytes, whereas TGF-?2 significantly reduced metabolism. OPN signaling via CD44 mediated a repressive outcome on metabolic activity, whereas signaling via integrin receptors resulted in a pro-metabolic effect. In summary, our findings characterize OPN as a TGF-?2 responsive factor that is not involved in TGF-?2 mediated ECM and HSP modulation, but affects the metabolic activity of astrocytes. A potential involvement in a protective response to TGF-?2 triggered damage is indicated, but requires further investigation.
EVALuna2:4415

Palate Lung Nasal Clone (PLUNC), a Novel Protein of the Tear Film: Three-Dimensional Structure, Immune Activation, and Involvement in Dry Eye Disease (DED) - Schicht, Martin; Rausch, Felix; Beron, Martin; Jacobi, Christina; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Kruse, Friedrich; Bräuer, Lars; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2015)
Palate Lung Nasal Clone (PLUNC) is a hydrophobic protein belonging to the family of surfactant proteins that is involved in fluid balance regulation of the lung. Moreover, it is known to directly act against gram-negative bacteria. The purpose of this study was to investigate the possible expression and antimicrobial role of PLUNC at the healthy ocular surface and in tears of patients suffering from dry eye disease (DED).Bioinformatics and biochemical and immunologic methods were combined to elucidate the structure and function of PLUNC at the ocular surface. Tissue-specific localization was performed by using immunohistochemistry. The PLUNC levels in tear samples from non-Sjögren's DED patients with moderate dry eye suffering either from hyperevaporation or tear deficiency were analyzed by ELISA and compared with tears from healthy volunteers.Palate Lung Nasal Clone is expressed under healthy conditions at the ocular surface and secreted into the tear film. Protein modeling studies and molecular dynamics simulations performed indicated surface activity of PLUNC. In vitro experiments revealed that proinflammatory cytokines and bacterial supernatants have only a slight effect on the expression of PLUNC in HCE and HCjE cell lines. In tears from DED patients, the PLUNC concentration is significantly increased (7-fold in evaporative dry eye tears and 17-fold in tears from patients with tear deficiency) compared with healthy subjects.The results show that PLUNC is a protein of the tear film and suggest that it plays a role in fluid balance and surface tension regulation at the ocular surface.
EVALuna2:4442

Pathophysiology of Meibomian Glands - An Overview - Dietrich, Jana; Garreis, Fabian; Paulsen, Friedrich (Ocular Immunology and Inflammation, 2021)
Purpose: The meibomian glands are located in the tarsal plate of the upper and lower eyelid and are responsible for the production of a lipid-rich secretion, the meibum, which forms the outer component of the tear film. Meibomian gland dysfunction results in excessive evaporation of the tear film and is the leading cause of dry eye disease (DED). Despite the high prevalence of DED, the etiology of meibomian gland dysfunction is only basically understood. In addition, the molecular mechanisms of meibomian gland maturation and physiological function are currently the focus of research. Methods: A systematic literature search was performed using the main scientific databases, including all relevant published articles up to September 2020. Results: This article provides an overview of the current state of knowledge about meibomian gland stem cells, cell surface marker expression and PPAR gamma signaling, as well as the pathological causes of meibomian gland dysfunction. Conclusion: Androgen deficiency, hyperkeratinization, PPAR gamma signaling and inflammatory reactions including neutrophil extracellular traps (NETs) seem to be key factors within the pathological processes of the meibomian gland.
CRIS-Team WoS Importer:2021-05-28

Plasma gelsolin promotes re-epithelialization - Wittmann, Johannes; Dieckow, J.; Schröder, Henrik; Hampel, Ulrike; Garreis, Fabian; Jacobi, Christina; Milczarek, Aleksandra; Hsieh, K. L.; Pulli, Benjamin; Chen, J. W.; Hoogeboom, S.; Bräuer, Lars; et al. (Scientific Reports, 2018)
Woundhealing disorders characterized by impaired or delayed re-epithelialization are a serious medical problem that is painful and difficult to treat. Gelsolin (GSN), a known actin modulator, supports epithelial cell regeneration and apoptosis. The aim of this study was to estimate the potential of recombinant gelsolin (rhu-pGSN) for ocular surface regeneration to establish a novel therapy for delayed or complicated wound healing. We analyzed the influence of gelsolin on cell proliferation and wound healing in vitro, in vivo/ex vivo and by gene knockdown. Gelsolin is expressed in all tested tissues of the ocular system as shown by molecular analysis. The concentration of GSN is significantly increased in tear fluid samples of patients with dry eye disease. rhu-pGSN induces cell proliferation and faster wound healing in vitro as well as in vivo/ex vivo. TGF-β dependent transcription of SMA is significantly decreased after GSN gene knockdown. Gelsolin is an inherent protein of the ocular system and is secreted into the tear fluid. Our results show a positive effect on corneal cell proliferation and wound healing. Furthermore, GSN regulates the synthesis of SMA in myofibroblasts, which establishes GSN as a key protein of TGF-β dependent cell differentiation.
EVALuna2:35306

Production and Secretion of Gelsolin by Both Human Macrophage- and Fibroblast-like Synoviocytes and GSN Modulation in the Synovial Fluid of Patients with Various Forms of Arthritis - Feldt, Jessica; Schicht, Martin; Welss, Jessica; Gelse, Kolja; Sesselmann, Stefan; Tsokos, Michael; Socher, Eileen; Garreis, Fabian; Mueller, Thomas; Paulsen, Friedrich (Biomedicines, 2022)
Gelsolin (GSN) is an actin-binding protein involved in cell formation, metabolism and wound closure processes. Since this protein is known to play a role in arthritis, here we investigate how the synovial membrane with its specific synoviocytes contributes to the expression of GSN and how the amount of GSN expressed is modulated by different types of arthritis. Synovial membranes from adult healthy subjects and patients with rheumatoid arthritis (RA) and osteoarthritis (OA) are analyzed by immunofluorescence, Western blot and ELISA. Macrophage-like synoviocytes (MLS) and fibroblast-like synoviocytes (FLS) were isolated, cultured and analyzed for their potential to produce and secrete GSN. In addition, the GSN concentrations in the synovial fluid of various forms of arthritis are determined by ELISA. GSN is produced by the healthy and arthritic synovial membranes. Both forms of synoviocytes (MLS and FLS) release GSN. The results show that there is a significant reduction in GSN in the synovial fluid in adult patients with OA. This reduction is also detectable in adult patients with RA but is not as evident. In juvenile arthritis, there is a slight increase in GSN concentration in the synovial fluid. This study shows that primary MLS and FLS express GSN and that these cells, in addition to articular chondrocytes, contribute to GSN levels in synovial fluid. Furthermore, GSN concentrations are modulated in different types of arthritis. Further studies are needed to fully understand how GSN is involved in joint homeostasis.<br
Keywords: arthritis; gelsolin; synovial fluid; synoviocytes

Prolactin Inducible Protein, but Not Prolactin, Is Present in Human Tears, Is Involved in Tear Film Quality, and Influences Evaporative Dry Eye Disease - Jüngert, Katharina; Paulsen, Friedrich; Jacobi, Christina; Horwath-Winter, Jutta; Garreis, Fabian (Frontiers in Medicine, 2022)
PurposeDecreased production of the aqueous component of the tear film is an important cause of the development of dry eye disease (DED). Tear production is influenced by hormones and hormone-like factors. Prolactin (PLR), a multifunctional pituitary gland hormone, is regularly present in the lacrimal gland of rats and rabbits. In humans, serum PLR concentration correlates with tear quality. To gain deeper insights of possible effects of PRL, prolactin receptor (PRLR) and prolactin inducible protein (PIP), we analyzed the three proteins in the human lacrimal apparatus and in reflex tears of healthy volunteers as well as patients suffering from DED. MethodsGene expression of PRLR and PIP was analyzed by RT-PCR in cadaveric human lacrimal gland and ocular surface tissues, immortalized human corneal epithelial cells (HCE and hTEPI) and human Meibomian gland epithelial cells (HMGECs). At the protein level, the expression and localization of PRL, PRLR and PIP in formalin-fixed paraffin sections of the lacrimal apparatus were studied by immunohistochemistry. In addition, tear fluid from DED patients and healthy volunteers was analyzed by ELISA to determine the concentration of PRL and PIP. ResultsRT-PCR analyses revealed gene expression of PRLR and PIP in human tissue samples of cornea, lacrimal glands, and eyelids, whereas only PIP, but not PRLR, was detectable in immortalized corneal epithelial cells. Immunohistochemistry revealed for the first time the expression and localization of PRL, PRLR, and PIP in human tissues of the lacrimal apparatus and at the ocular surface. PRL and PRLR were detectable in corneal epithelium, lacrimal glands, and Meibomian glands. Reflex tears from DED patients revealed significantly increased PIP concentrations, whereas PRL was undetectable in tears of DED patients and healthy volunteers. ConclusionPRL, PRLR, and PIP are found in the lacrimal apparatus and on the ocular surface. PIP, but not PRL, is present in human tears and appears to be involved in the physiology of tear film quality. Our clinical data revealed that PIP may affect tear quality, but further functional analyses are needed to fully elucidate the effects of PRL and PIP-associated factors in tear secretion as well as in the connection of DED.
CRIS-Team WoS Importer:2022-07-29

Quantification of surfactant proteins in tears of patients suffering from dry eye disease compared to healthy subjects - Posa, Andreas; Paulsen, Friedrich; Dietz, Richard; Garreis, Fabian; Sander, Ralph; Schicht, Martin; Sel, Saadettin; Scholz, Michael; Hammer, Christian; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2018)
PURPOSE: To quantify and compare the amounts of surfactant proteins SP-A, SP-B, SP-C and SP-D in the tear fluid collected from patients with dry eye syndrome and from individuals with a healthy ocular surface. METHODS: Schirmer strips were used to collect tear fluid from both eyes of 241 volunteers (99 men, 142 women; age range: 18-87 years). Dry eye syndrome was diagnosed by ophthalmologists in 125 patients, whereas the healthy control group comprised 116 individuals. The total protein concentration was determined via Bradford assay. The relative concentration of surfactant proteins SP-A through -D was measured by enzyme-linked immuno-sorbent assay (ELISA). RESULTS: The mean relative concentrations of SP-A, SP-C and SP-D were significantly higher in the dry eye group as compared to the healthy controls (p<0.05, one-way ANOVA). SP-B was also detected at a higher concentration in the dry eye group, but the difference to the control group was not statistically significant. CONCLUSIONS: The upregulation of SP-A and SP-D in the dry eye group is probably related to these proteins' known antimicrobial and immunomodulatory effects at the ocular surface. It may represent a pathophysiological response to the inflammatory condition of the ocular surface in dry eye. The upregulation of SP-B and SP-C may represent an effort of the lacrimal system to reduce surface tension and thus to counteract the increased tendency of the tear film to tear in dry eye.
EVALuna2:35321

Relaxin 2 is functional at the ocular surface and promotes corneal wound healing - Hampel, Ulrike; Klonisch, Thomas; Sel, Saadettin; Schulze, Ute; Garreis, Fabian; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2012)
We aimed to determine if the insulin-like peptide hormone relaxin 2 (RLN2) is expressed at the ocular surface and in tears and if RLN2 influences wound healing at the ocular surface, which is associated with extracellular matrix (ECM) remodeling.We analyzed transcript levels of human RLN2 and its cognate relaxin-like receptors RXFP1 and RXFP2 in tissues of the ocular surface, lacrimal apparatus, and human corneal (HCE), conjunctival (HCjE) and sebaceous (SC) cell lines. We analyzed effects of human RLN2 on cell proliferation and migration and quantified mRNA expression of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in HCE, HCjE, and SC. Using an alkali-induced corneal wounding model, we analyzed the wound healing rate in C57BL/6 mice eyes after topically applied RLN2.The presence of RLN2, RXFP1, and RXFP2 transcripts was detected in lacrimal gland, eyelid, conjunctiva, cornea, primary corneal fibroblasts, nasolacrimal ducts, and all three cell lines. ELISA revealed RLN2 protein in all ocular surface tissues analyzed and in human tears. Stimulation of HCE, HCjE, and SC with RLN2 significantly increased cell proliferation and migration. Relative mRNA expression levels of MMP2, MMP9, TIMP1, and TIMP2 were significantly influenced by RLN2 in all three cell lines at different time points studied. The local application of RLN2 onto denuded corneal surface resulted in significantly elevated corneal wound healing.Our data support a novel role for the RLN2 ligand-receptor system at the ocular surface and in the lacrimal apparatus as a potential future therapeutic during wound healing at the ocular surface.
EVALuna2:4369

Serum-induced keratinization processes in an immortalized human meibomian gland epithelial cell line - Hampel, Ulrike; Schröder, Antje; Mitchell, Todd; Brown, Simon; Snikeris, Peta; Garreis, Fabian; Kunnen, Carolina; Willcox, Mark; Paulsen, Friedrich (PLoS ONE, 2015)
The aim of this study was to evaluate a human meibomian gland epithelial cell line (HMGEC) as a model for meibomian gland (patho)physiology in vitro.HMGEC were cultured in the absence or presence of serum. Sudan III lipid staining, ultrastructural analysis and lipidomic analyses were performed. Impedance sensing, desmoplakin 1/2 mRNA and cytokeratin (CK) 1, 5, 6, 14 levels were evaluated. Serum containing medium supplemented with higher serum, glucose, an omega-3 lipid cocktail, eicosapentaenoic acid or sebomed medium were investigated for lipid accumulation and ultrastructural morphology.Lipid droplet accumulation in HMGEC was induced by serum containing media after 1 day, but decreased over time. Cultivation in serum induced desmosome and cytokeratin filament formation. Desmoplakin 1/2 gene levels were significantly upregulated after 1d of serum treatment. Furthermore, the normalized impedance increased significantly. Lipidome analysis revealed high levels of phospholipids (over 50%), but very low levels of wax ester and cholesteryl esters (under 1%). Stimulation with eicosapentaenoic acid increased lipid accumulation after one day.Serum treatment of HMGEC caused lipid droplet formation to some extent but also induced keratinization. The cells did not produce typical meibum lipids under these growth conditions. HMGEC are well suited to study (hyper)keratinization processes of meibomian gland epithelial cells in vitro.
EVALuna2:4445

SFTA3, a novel protein of the lung: three-dimensional structure, characterisation and immune activation - Schicht, Martin; Rausch, Felix; Finotto, Susetta; Mathews, Martina; Mattil, Anja; Schubert, Melanie; Koch, Beate; Traxdorf, Maximilian; Bohr, Christopher; Worlitzsch, Dieter; Brandt, Wolfgang; Garreis, Fabian; et al. (European Respiratory Journal, 2014)
The lung constantly interacts with numerous pathogens. Thus, complex local immune defence mechanisms are essential to recognise and dispose of these intruders. This work describes the detection, characterisation and three-dimensional structure of a novel protein of the lung (surfactant-associated protein 3 (SFTA3/SP-H)) with putative immunological features. Bioinformatics, biochemical and immunological methods were combined to elucidate the structure and function of SFTA3. The tissue-specific detection and characterisation was performed by using electron microscopy as well as fluorescence imaging. Three-dimensional structure generation and analysis led to the development of specific antibodies and, as a consequence, to the localisation of a novel protein in human lung under consideration of cystic fibrosis, asthma and sepsis. In vitro experiments revealed that lipopolysaccharide induces expression of SFTA3 in the human lung alveolar type II cell line A549. By contrast, the inflammatory cytokines interleukin (IL)-1? and IL-23 inhibit expression of SFTA3 in A549. Sequence- and structure-based prediction analysis indicated that the novel protein is likely to belong to the family of lung surfactant proteins. The results suggest that SFTA3 is an immunoregulatory protein of the lung with relevant protective functions during inflammation at the mucosal sites.
EVALuna2:4400

SFTA3 - a novel surfactant protein of the ocular surface and its role in corneal wound healing and tear film surface tension - Schicht, Martin; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Jacobi, Christina; Sahin, Afsun; Holland, Detlef; Schröder, Henrik; Hammer, Christian; Paulsen, Friedrich; Bräuer, Lars (Scientific Reports, 2018)
The study aimed to characterize the expression and function of SFTA3 at the ocular surface and in tears. Ocular tissues, conjunctival (HCjE) and human corneal (HCE) epithelial cell lines as well as tearfilm of patients suffering from different forms of dry eye disease (DED) were analyzed by means of RT-PCR, western blot, immunohistochemistry, and ELISA. A possible role of recombinant SFTA3 in corneal wound healing was investigated performing in vitro scratch assays. Tear film regulatory properties were analyzed with the spinning drop method and the regulation of SFTA3 transcripts was studied in HCE and HCjE after incubation with proinflammatory cytokines as well as typical ocular pathogens by real-time RT-PCR and ELISA. The results reveal that human ocular tissue as well as tears of healthy volunteers express SFTA3 whereas tears from patients with DED showed significantly increased SFTA3 levels. In vitro wounding of HCE cell cultures that had been treated with recombinant SFTA3 demonstrated a significantly increased wound closure rate and rSFTA3 reduced the surface tension of tear fluid. The results indicate that SFTA3 at the ocular surface seemed to be involved in wound healing and the reduction of surface tension.
EVALuna2:35316

Structure, regulation and related diseases of the actin-binding protein gelsolin - Feldt, Jessica; Schicht, Martin; Garreis, Fabian; Welss, Jessica; Schneider, Ulrich W.; Paulsen, Friedrich (Expert Reviews in Molecular Medicine, 2019)
Gelsolin (GSN), one of the most abundant actin-binding proteins, is involved in cell motility, shape and metabolism. As a member of the GSN superfamily, GSN is a highly structured protein in eukaryotic cells that can be regulated by calcium concentration, intracellular pH, temperature and phosphatidylinositol-4,5-bisphosphate. GSN plays an important role in cellular mechanisms as well as in different cellular interactions. Because of its participation in immunologic processes and its interaction with different cells of the immune system, GSN is a potential candidate for various therapeutic applications. In this review, we summarise the structure of GSN as well as its regulating and functional roles, focusing on distinct diseases such as Alzheimer's disease, rheumatoid arthritis and cancer. A short overview of GSN as a therapeutic target in today's medicine is also provided.
CRIS-Team WoS Importer:2019-02-27

Surfactant protein H is part of the tear film, lowers surface tension, is increased in dry eye disease and accelerates corneal wound healing - Paulsen, Friedrich; Hartjen, Nadine; Beilicke, Stephanie; Garreis, Fabian; Jacobi, Christina; Sahin, Afsun; Holland, Detlev; Bräuer, Lars; Schicht, Martin (2018)
EVALuna2:35310

Surfactant proteins of the human larynx - Sheats, Michelle; Schröder, Henrik; Rauscha, F.; Bohr, Christopher; Kißlinger, Franziska; De Tristan, J.; Iro, Heinrich; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: Surfactant proteins (SPs) originally identified in lung tissue are important players in the innate immune system. Beyond this, they contribute to stability and rheology of gaseous or aqueous interphases. In the present study, we determined the expression and presence of SPs (A, B, C and D) in different areas of the human larynx. METHODS: mRNA expression of SP-A, -B, -C and -D was analyzed by means of RT-PCR in healthy samples of epiglottis, vocal and vestibular folds, subglottis and trachea. Distribution and localization of all four SPs were analyzed by Western blot and immunohistochemistry in healthy human tissue samples. RESULTS: All four SPs were detected at the mRNA- and protein level in the human larynx as well as by means of immunohistochemistry in the different tissue samples of the human larynx. CONCLUSION: The results reveal that all four SPs are produced with different expression patterns within the human larynx. Based on the known functions, our results suggest that SPs might be involved in maintaining mucus rheology and subsequently they could be essential components for proper phonation. Moreover, the proteins seem to play a role in immune defense of the larynx.
EVALuna2:33358

Teaching to Relax: Development of a Program to Potentiate Stress—Results of a Feasibility Study with Medical Undergraduate Students - Scholz, Michael; Neumann, Carolin; Wild, Katharina; Garreis, Fabian; Hammer, Christian; Ropohl, Axel; Paulsen, Friedrich; Burger, Pascal H. M. (Applied Psychophysiology and Biofeedback, 2016)
Medical students are a population at risk for the development of stress-related risk states (e.g. burnout) and manifest mental disorders (e.g. depression). Still the learning of coping mechanisms against stress is not an integral part of the medical curriculum. In a pilot study we developed an elective course for learning relaxation techniques (Relacs) which was geared to the clinical practice of autogenic training (AT) with psychiatric patients. The course focussed on an innovative and mostly communicative transfer of knowledge about AT, progressive muscle relaxation and medical hypnosis and stressed the principle of repeated and supervised exercises in small student groups alongside self-administered exercise. 42 students took part in this course and showed a very high acceptance for the topic and positive evaluation. Moreover, we found a distinct improvement of the participants’ mental parameters (burnout, anxiety) and a good knowledge about the course’s contents within the final exams at the end of the semester. The structure and realisation of the course is easily adaptable and very effective regarding the improvement of the students’ mental health. Due to our results and the commonly known prevalence of stress-related disorders in medical students we postulate the integration of courses on relaxation strategies in the medical curriculum.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autogenic training; Burnout; Medical education; Medical hypnosis; Progressive muscle relaxation

The human meibomian gland epithelial cell line as a model to study meibomian gland dysfunction - Hampel, Ulrike; Garreis, Fabian (Experimental Eye Research, 2017)
The meibomian gland dysfunction (MGD) is the leading cause of dry eye disease (DED) throughout the world. The investigation of MGD lacks suitable in vivo and in vitro models. In 2010 a human meibomian gland epithelial cell line (HMGEC) was established, so far the only available meibomian gland cell line. The characterization of HMGEC is of major importance to clarify its suitability for studying the meibomian gland (patho)physiology in vitro. The current culture protocol and new concepts of HMGEC culture will be compared. Hormones are believed to be a key factor in meibomian gland dysfunction thus HMGEC responsiveness to hormone stimulation is crucial to elucidate the hormonal influence on the meibomian gland. This review will summarize current findings about HMGEC and discuss its role in the meibomian gland dysfunction research.
EVALuna2:35327

The novel surfactant protein SP-H enhances the phagocytosis efficiency of macrophage-like cell lines U937 and MH-S - Diler, Ebru; Schicht, Martin; Rabung, Andrea; Tschernig, Thomas; Meier, Carola; Rausch, Felix; Garreis, Fabian; Bräuer, Lars; Paulsen, Friedrich (BMC Research Notes, 2014)
Surfactant proteins (SP) secreted by alveolar type 2 cells, play an essential role in maintaining the air-liquid barrier of the lung and are also involved in the opsonisation and clearance of bacteria by phagocytes. We have recently described a novel surfactant protein, SP-H (SFTA3). Expression of SP-H was earlier demonstrated to be upregulated by LPS and negatively regulated by IL-1? and IL-23 in vitro. The influence of SP-H on phagocytosis was measured using a murine and a human phagocytic cell line and fluorescent latex beads.SP-H markedly increases phagocytosis in vitro in the murine-derived alveolar macrophage cell lines MH-S and in human-derived differentiated U937 cells.It can be assumed that SP-H is involved in regulating phagocytic activity of macrophages. SP-H is a new player in pulmonary host defence.
EVALuna2:4439

The Potential Role of SP-G as Surface Tension Regulator in Tear Film: From Molecular Simulations to Experimental Observations - Schicht, Martin; Riedlova, Kamila; Kukulka, Mercedes; Li, Wenyue; Scheer, Aurelius; Garreis, Fabian; Jacobi, Christina; Paulsen, Friedrich; Cwiklik, Lukasz; Bräuer, Lars (International Journal of Molecular Sciences, 2022)
The ocular surface is in constant interaction with the environment and with numerous pathogens. Therefore, complex mechanisms such as a stable tear film and local immune defense mechanisms are required to protect the eye. This study describes the detection, characterization, and putative role of surfactant protein G (SP-G/SFTA2) with respect to wound healing and surface activity. Bioinformatic, biochemical, and immunological methods were combined to elucidate the role of SP-G in tear film. The results show the presence of SP-G in ocular surface tissues and tear film (TF). Increased expression of SP-G was demonstrated in TF of patients with dry eye disease (DED). Addition of recombinant SP-G in combination with lipids led to an accelerated wound healing of human corneal cells as well as to a reduction of TF surface tension. Molecular modeling of TF suggest that SP-G may regulate tear film surface tension and improve its stability through specific interactions with lipids components of the tear film. In conclusion, SP-G is an ocular surface protein with putative wound healing properties that can also reduce the surface tension of the tear film.
CRIS-Team WoS Importer:2022-06-10

Thermosensitive TRP Channels Are Functionally Expressed and Influence the Lipogenesis in Human Meibomian Gland Cells - Keller, Melina; Mergler, Stefan; Li, Aruna; Zahn, Ingrid; Paulsen, Friedrich; Garreis, Fabian (International Journal of Molecular Sciences, 2024)
While the involvement of thermosensitive transient receptor potential channels (TRPs) in dry eye disease (DED) has been known for years, their expression in the meibomian gland (MG) has never been investigated. This study aims to show their expression and involvement in the lipogenesis of the MG, providing a possible new drug target in the treatment of DED. Our RT-PCR, Western blot and immunofluorescence analysis showed the expression of TRPV1, TRPV3, TRPV4 and TRPM8 in the MG at the gene and the protein level. RT-PCR also showed gene expression of TRPV2 but not TRPA1. Calcium imaging and planar patch-clamping performed on an immortalized human meibomian gland epithelial cell line (hMGECs) demonstrated increasing whole-cell currents after the application of capsaicin (TRPV1) or icilin (TRPM8). Decreasing whole-cell currents could be registered after the application of AMG9810 (TRPV1) or AMTB (TRPM8). Oil red O staining on hMGECs showed an increase in lipid expression after TRPV1 activation and a decrease after TRPM8 activation. We conclude that thermo-TRPs are expressed at the gene and the protein level in MGs. Moreover, TRPV1 and TRPM8’s functional expression and their contribution to their lipid expression could be demonstrated. Therefore, TRPs are potential drug targets and their clinical relevance in the therapy of meibomian gland dysfunction requires further investigation.
CRIS-Team Scopus Importer:2024-04-26
Keywords: dry eye disease; meibomian gland; meibomian gland dysfunction; tear film; thermo-TRPs; TRP channels

The Translational Role of MUC8 in Salivary Glands: A Potential Biomarker for Salivary Stone Disease? - Schicht, Martin; Reichle, Adrian; Schapher, Mirco; Garreis, Fabian; Kleinsasser, Benedikt; Aydin, Malik; Sahin, Afsun; Iro, Heinrich; Paulsen, Friedrich (Diagnostics, 2021)
Mucin (MUC) 8 has been shown to play an important role in respiratory disease and inflammatory responses. In the present study, we investigated the question of whether MUC8 is also produced and secreted by salivary glands and whether it may also play a role in the oral cavity in the context of inflammatory processes or in the context of salivary stone formation. Tissue samples from parotid and submandibular glands of body donors (n = 6, age range 63-88 years), as well as surgically removed salivary stones from patients (n = 38, age range 48-72 years) with parotid and submandibular stone disease were immunohistochemically analyzed targeting MUC8 and TNF alpha. The presence of MUC8 in salivary stones was additionally analyzed by dot blot analyses. Moreover, saliva samples from patients (n = 10, age range 51-72 years), who had a salivary stone of the submandibular gland on one side were compared with saliva samples from the other "healthy " side, which did not have a salivary stone, by ELISA. Positive MUC8 was detectable in the inter- and intralobular excretory ducts of both glands (parotid and submandibular). The glandular acini showed no reactivity. TNF alpha revealed comparable reactivity to MUC8 in the glandular excretory ducts and also did not react in glandular acini. Salivary stones demonstrated a characteristic distribution pattern of MUC8 that differed between parotid and submandibular salivary stones. The mean MUC8 concentration was 71.06 ng/mL in female and 33.21 ng/mL in male subjects (p = 0.156). Saliva from the side with salivary calculi contained significantly (15-fold) higher MUC8 concentration levels than saliva from the healthy side (p = 0.0005). MUC8 concentration in salivary stones varied from 4.59 ng/mL to 202.83 ng/mL. In females, the MUC8 concentration in salivary stones was significantly (2.3-fold) higher, with an average of 82.84 ng/mL compared to 25.27 ng/mL in male patients (p = 0.034). MUC8 is secreted in the excretory duct system of salivary glands and released into saliva. Importantly, MUC8 salivary concentrations vary greatly between individuals. In addition, the MUC8 concentration is gender-dependent (& FEMALE; > & MALE;). In the context of salivary stone diseases, MUC8 is highly secreted in saliva. The findings support a role for MUC8 in the context of inflammatory events and salivary stone formation. The findings allow conclusions on a gender-dependent component of MUC8.
CRIS-Team WoS Importer:2022-01-14

Upregulation of Transient Receptor Potential Vanilloid Type-1 Channel Activity and Ca2+ Influx Dysfunction in Human Pterygial Cells - Garreis, Fabian; Schröder, Antje; Reinach, Peter S.; Zoll, Stefanie; Khajavi, Noushafarin; Dhandapani, Priyavathi; Lucius, Alexander; Pleyer, Uwe; Paulsen, Friedrich; Mergler, Stefan (Investigative Ophthalmology & Visual Science, 2016)
PURPOSE: The heat-sensitive transient receptor potential vanilloid type-1 (TRPV1) channel (i.e., capsaicin [CAP] receptor) is upregulated in numerous cancers. This study determined if this response occurs in fresh and cultured hyperplastic human pterygial epithelial tissues. METHODS: Reverse transcriptase PCR and quantitative real-time PCR, along with immunohistochemistry and Western blotting, characterized TRPV1 expression patterns in pterygial and healthy conjunctival tissue, primary and immortalized pterygial cells (hPtEC), and primary and immortalized conjunctival epithelial cells (HCjEC). Imaging of Ca2+ and planar whole-cell patch-clamping evaluated TRP channel activity. An MTS assay measured cell metabolic activity and a cell growth assay monitored proliferation. RESULTS: Capsaicin (20 μM) and elevating bath temperature above 43°C activated Ca2+ transients more in hPtEC than HCjEC. Capsaicin induced corresponding changes in inward currents that were inhibited by 20 μM capsazepine (CPZ). Vascular endothelial growth factor (VEGF) also increased Ca2+-influx and induced corresponding inward currents more in hPtEC than in HCjEC, whereas CPZ (20 μM), BCTC (20 μM), or La3+ (500 μM) reduced these responses, respectively. Whereas epidermal growth factor (EGF) increased proliferation more in hPtEC than in HCjEC, VEGF had no effect on this response. Capsazepine suppressed hPtEC proliferation induced by EGF and VEGF, whereas it was cytotoxic to HCjEC. CONCLUSIONS: Mitogenic responses to EGF and VEGF are mediated through TRPV1 transactivation. Only in hPtEC do the increases in proliferation induced by EGF exceed those in HCjEC. Therefore, TRPV1 is a potential drug target whose clinical relevance in treating pterygium warrants further assessment.
EVALuna2:35348

Vascular Endothelial Growth Factor (VEGF) Induced Downstream Responses to Transient Receptor Potential Vanilloid 1 (TRPV1) and 3-Iodothyronamine (3-T1AM) in Human Corneal Keratocytes - Tuerker, Ersal; Garreis, Fabian; Khajavi, Noushafarin; Reinach, Peter S.; Joshi, Pooja; Brockmann, Tobias; Lucius, Alexander; Ljubojevic, Nina; Turan, Elizabeth; Cooper, Drew; Schick, Felix; Reinholz, Rob; et al. (Frontiers in Endocrinology, 2018)
This study was undertaken to determine if crosstalk among the transient receptor potential (TRP) melastatin 8 (TRPM8), TRP vanilloid 1 (TRPV1), and vascular endothelial growth factor (VEGF) receptor triad modulates VEGF-induced Ca2+ signaling in human corneal keratocytes. Using RT-PCR, qPCR and immunohistochemistry, we determined TRPV1 and TRPM8 gene and protein coexpression in a human corneal keratocyte cell line (HCK) and human corneal cross sections. Fluorescence Ca2+ imaging using both a photomultiplier and a single cell digital imaging system as well as planar patch-clamping measured relative intracellular Ca2+ levels and underlying whole-cell currents. The TRPV1 agonist capsaicin increased both intracellular Ca2+ levels and whole-cell currents, while the antagonist capsazepine (CPZ) inhibited them. VEGF-induced Ca2+ transients and rises in whole-cell currents were suppressed by CPZ, whereas a selective TRPM8 antagonist, AMTB, increased VEGF signaling. In contrast, an endogenous thyroid hormone-derived metabolite 3-Iodothyronamine (3-T1AM) suppressed increases in the VEGF-induced current. The TRPM8 agonist menthol increased the currents, while AMTB suppressed this response. The VEGF-induced increases in Ca2+ influx and their underlying ionic currents stem from crosstalk between VEGFR and TRPV1, which can be impeded by 3-T1AM-induced TRPM8 activation. Such suppression in turn blocks VEGF-induced TRPV1 activation. Therefore, crosstalk between TRPM8 and TRPV1 inhibits VEGFR-induced activation of TRPV1.
EVALuna2:35299

What drives Meibomian gland disease? - Paulsen, Friedrich; Garreis, Fabian (Archivos de la Sociedad Española de Oftalmología, 2014)
EVALuna2:4435